Impact of uncertainties in accelerometer modeling on the maximum values of absolute dynamic error. (February 2016) - Tomczyk, Krzysztof
Highlights: The review of literature concerning the dynamic errors is presented. The method for parameter estimation of accelerometers is discussed. The procedures for determining the maximum error are considered. Impact of the uncertainties on the value of error is discussed. The numerical calculations were executed in the MathCad14 program. Abstract: The paper considers the impact of uncertainties associated with estimated parameters of the accelerometer model on the maximum values of absolute dynamic error. Assessment of such impact constitutes a novelty in determination of the maximum values of absolute dynamic error. The parameter estimation method of the accelerometer mathematical model in the frequency domain and the procedure for calculation of the associated uncertainties under the current regulations, are discussed in detail in the second section of this paper. The procedures for determining the maximum values of absolute dynamic error generated at the output of an accelerometer, when the input signals are constrained in magnitude and both in magnitude and rate of change, are discussed in the third section. This dynamic error has been determined in relation to the standard represented by the 15-th order Butterworth filter. The possibilities of application of both the continuous and the discrete procedures of error calculation have also been presented. For the execution of numerical integration, the Romberg method has been applied. Based on theoretical consideration, the results of both the parameter estimation of the Endevco87 accelerometer and calculation of the corresponding uncertainties are presented in the fourth section. The fifth section is devoted to the presentation of the most important assumptions, which allow the determination of the maximum values of absolute dynamic error. An assessment of the impact of the uncertainties associated with the estimated parameters on the value of absolute error is discussed in the last section of this paper. The numerical calculations were executed in the MathCad14 program.